Clonal Multipotency of Neural Crest-Derived Stem/Progenitor Cells from Bulge Region of Adult Mammal Hair Follicle - Vasyliev, Roman G. (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(3):279–282.